Escuelas limpias: proyecto de gestión ambiental - Cárdenas, Pedro (2008)
Environmental problems, pollution and global warming can be addressed from different perspectives. This project seeks to be an effective proposal to address these issues. It directs its efforts to the development of a process of awareness of young Peruvians between the ages of 11 and 15, to be incorporated into public schools through a program of environmental education. It starts from identifying a district model with critical levels of pollution in which to promote and implement an appropriate environmental education to contribute to the improvement and welfare of the environment The Independencia district was selected for it shows acute health problems, pollution and poor environmental awareness and culture, with the whole purpose of changing the attitude of a group of young people, parents and teachers to the social and environmental problems of their environment, instilling in them awareness and training in environmental education to create a multiplier effect and to improve their quality of life.